Beta‐lactam hypersensitivity in children with cystic fibrosis: a study in a specialized pediatric center for cystic fibrosis and drug allergy. Issue 1 (18th November 2013) - Matar, Rania; Le Bourgeois, Muriel; Scheinmann, Pierre; de, Jacques; Ponvert, Claude
Abstract Background Beta‐lactam hypersensitivity (HS) is suspected in 5–12% of the children, but proven in only 10–15% of those children, based on skin and challenge tests results. In contrast, 30–60% of patients with cystic fibrosis (CF) are diagnosed allergic to beta‐lactams, based mainly on the clinical history of the patients. Objectives To confirm or rule out a suspected beta‐lactam HS in CF children and to determine the prevalences of suspected and confirmed beta‐lactam HS in those children. Patients and methods Children with CF and suspected beta‐lactam HS were explored by means of skin and challenge tests with the suspected and alternate beta‐lactams. The results in CF children were compared with those reported in the literature in non‐ CF children. Results Eight of the 701 CF children followed in our center between 1990 and 2011 (1.14%), and 11 other children from other centers were explored for suspected beta‐lactam HS. Beta‐lactam HS was diagnosed in nine of these children (47.3%). Based on the results in the children followed in our center, the prevalence of beta‐lactam HS was 0.71% (5/701) in CF children vs. a mean estimated prevalence of 1–1.5% in the general pediatric population. Conclusion Our results contrast with those of most previous studies. Although half of the CF children with suspected beta‐lactam HS were truly allergic to beta‐lactams, the general prevalence of beta‐lactam HS in CF children was very low. This may result from tolerance induced by frequent and/or prolonged treatments with beta‐lactams.